ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN MUARA ENIM - Ardhillatul Jannah, Sinta; Okmyarti Pratiwi, Mandy (Badan Penelitian dan Pengembangan Daerah KabupatenMuara Enim, 2022)
This study aims to determine the impact of the COVID-19 pandemic on local indigenous income (PAD) in Muara Enim Regency. The type of data used in this study is qualitative data with data collection techniques in the nature of a document study. Data analysis techniques in research use qualitative analysis techniques, which are methods that emphasize more on aspects of deep understanding of a problem than looking at problems for generalization research. The results of this study show that: The Original Regional Income (PAD) of Muara Enim Regency as a whole has decreased by 7.17% from 2019. The main cause of the decline in pad in Muara Enim Regency in 2020 is because the enactment of psbb and the existence of incentives or stimulus to taxpayers consisting of hotel tax, restaurant tax, entertainment tax, BPHTB and PBB P2 so that there is no local tax charge.